2022
DOI: 10.3390/ijerph19031760
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Is Associated with Improved Visuomotor Processing in Older Adults with Moderate and Advanced Glaucomatous Visual Field Defect: A Cross-Sectional Study

Abstract: Glaucoma affects a wide spectrum of daily essential activities in older adults. This study examined whether older adults with moderate and advanced stages of glaucoma exhibit differences in visuomotor task performance compared with age- and gender-matched ophthalmologically healthy control subjects and estimated the effects of physical activity (PA) levels, age, and severity of visual impairment on patients’ visuomotor task performance. Sixty older adults with moderate glaucoma, advanced glaucoma, and normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Using diffusion tensor MRI, Yang et al (2018) demonstrated that glaucomatous mice had extensive deterioration of visuomotor function by 9 months of age. Zwierko et al (2022) reported differences in visuomotor task performance among older adults with moderate and advanced glaucoma. Dive et al (2016) demonstrated visuomotor behavior in patients with glaucoma-related peripheral field reduction during the completion of natural movements.…”
Section: Discussionmentioning
confidence: 99%
“…Using diffusion tensor MRI, Yang et al (2018) demonstrated that glaucomatous mice had extensive deterioration of visuomotor function by 9 months of age. Zwierko et al (2022) reported differences in visuomotor task performance among older adults with moderate and advanced glaucoma. Dive et al (2016) demonstrated visuomotor behavior in patients with glaucoma-related peripheral field reduction during the completion of natural movements.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, patients with glaucoma exhibit white matter tract damage far beyond visual pathway localization 34 . Functionally, PACG patients show visual dysfunction and vision-related cortex dysfunction 35 , 36 . These studies suggest that PACG patients have abnormalities in their visual networks, both structurally and functionally.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, mice with glaucoma, characterized by heightened intraocular pressure, exhibited reduced fractional anisotropy and heightened radial diffusivity in the optic nerves and tract 34 . Functionally, PACG patients show visual dysfunction and vision-related cortex dysfunction 35,36 . These studies suggest that PACG patients have abnormalities in their visual networks, both structurally and functionally.…”
Section: Discussionmentioning
confidence: 99%